Potentiometric determination of antioxidant activity of extracts of Calendula Officinalis L. plants under the influence of growth biostimulants - Lupak, Oksana; Kovalchuk, Halyna; Antonyak, Halyna (ScienceRise: Biological Science, 2017)
There was determined the integral antioxidant activity of water and alcohol extracts of racemes of Calendula officinalis L. plants of the variety “Poliova krasunya”. Plants were cultivated in Precarpathian zone of Ukraine at the learning-research plot of Drogobych state pedagogical university, named after Ivan Franko at introduction of growth biostimulants “Vermibiomag”, “Vermiiodis” and “Vermistim”. The determination of antioxidant activity was realized by the potentiometric method, modified in the authors’ research using mediator system, based on the method of Brainina and co-authors and Aronbaev and co-authors. It was elucidated, that alcohol extracts of C. officinalis plants demonstrate antioxidant activity 1,5 – 1,6 times higher than water ones. Plants, cultivated under the effect of biostimulants have the higher antioxidant activity comparing with the control (without introducing biostimulants). Introduction of “Verbiomag” biostimulator to a greatest extent favored the growth of antioxidant activity of both alcohol (by 22,9 % more than the control) and water extracts (by 24,2 % higher than the control)